We remember with reverence and love : American Jews and the myth of silence after the Holocaust, 1945 - 1962 - Diner, Hasia R. 1946- (New York Univ. Press, 2009)
Introduction: Deeds and words -- Fitting memorials -- Telling the world -- The saving remnant -- Germany on their minds -- Wrestling with the postwar world -- Facing the Jewish future -- Conclusion: The corruption of history, the betrayal of memory